Individualized approach to primary prevention of substance use disorder: age-related risks - Eric Afuseh; Caitlin A. Pike; Ukamaka M. Oruche (BMC, 2020)
Abstract Background The misuse of legal and illegal substances has led to an increase in substance use disorder (SUD) in the United States. Although primary prevention strategies have been successfully used to target chronic physical diseases, these strategies have been less effective with SUD, given misconceptions of SUD, shortages in behavioral health professionals, and the population-based focus on specific substances. A developmental approach to the identification and primary prevention of SUD that does not fully rely upon behavioral health workers is needed. The purpose of this paper was to examine age related risk factors for developing SUD and present a novel individualized approach to SUD prevention. Methods A literature search was conducted to identify risk factors for SUD among children, young adults, adults, and older adults. We searched CINAHL, PsycINFO, and PubMed between the years 1989-2019, and extracted data, analyzing similarities and differences in risk factors across life stages. Broader categories emerged that were used to group the risk factors. Results More than 370 articles were found. Across all age groups, risk factors included adverse childhood experiences, trauma, chronic health diseases, environmental factors, family history, social determinants, and grief and loss. Despite the similarities, the contextual factors and life challenges associated with these risks varied according to the various life stages. We proposed an approach to primary prevention of SUD based on risk factors for developing the disease according to different age groups. This approach emphasizes screening, education, and empowerment (SEE), wherein individuals are screened for risk factors according to their age group, and screening results are used to customize interventions in the form of education and empowerment. Given that trained persons, including non-healthcare providers, close to the at-risk individual could conduct the screening and then educate and mentor the individual according to the risk level, the number of people who develop SUD could decrease. Conclusions The risk factors for developing SUD vary across the various life stages, which suggests that individualized approaches that do not overtax behavioral healthcare workers are needed. Using SEE may foster early identification and individualized prevention of SUD.